Proposed Business Strategy to Increase Sales and Competitiveness of Guci Swalayan Payakumbuh - Fikri Rasyidin, Muhammad; Wandebori, Harimukti (Journal of Accounting and Finance Management, 2025)
The retail sector has emerged as a critical component of Indonesia's economy, as a result of the increasing demand for modern, efficient shopping experiences and the changing behavior of consumers. Payakumbuh-based supermarket Guci Swalayan faces significant challenges, including stagnant sales. The total sales decreased to Rp48.59 billion in 2024, resulting in a negative growth rate of -0.85%. Guci Swalayan's performance has been adversely affected by weaknesses in marketing strategies, inconsistent service quality, and operational inefficiencies, despite the retail industry's expansion. This investigation evaluates the market position and competitiveness of Guci Swalayan by employing analytical tools such as Value Chain Analysis, VRIO Framework, PESTEL Analysis, Porter's Five Forces, and Competitor Analysis. The results indicate that Guci Swalayan has been unable to fully capitalize on the broader retail recovery. The company's sales have been stagnant due to factors such as inconsistent customer service (People score 2.71/5) and ineffective marketing (promotion score 2.23/5). In order to improve Guci Swalayan's market the primary actions needed are optimization of inventory management, human resource development, promotional campaigns, digital marketing and expanding the supermarket's parking capacity and reorganizing the store layout. These strategies can help Guci Swalayan increase customer loyalty, optimize sales processes, and ensure future profitability.